ANALISIS MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI - Mega Cantika; Olivia Febrianti; Sudirman Rizki Ariyanto; Muhammad Anasrulloh; Muhammad Yandi Pratama (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
Entrepreneurship is the effort of individuals who want to create or run a business or business. In college, there are entrepreneurship lessons that are useful to grow students' interest in entrepreneurship. This research aims to find out the extent of interest of students of economic education, Bhinneka PGRI Tulungagung University in entrepreneurship. This research is quantitative descriptive research. Data collection is carried out by distributing questionnaires to students of Economic Education Class of 2019. The research findings showed that of the 10 indicators in analyzing students' interest in entrepreneurship, only two indicators had a low percentage below 50%, namely the belief in being a successful entrepreneur and entrepreneurial ability with a percentage of 26.80% and 47.10%. While the other 8 indicators have a high percentage above 50%. Therefore, it can be concluded that the majority of students of the Economic Education Study Program of Bhinneka PGRI University have a high interest in entrepreneurship.